Efeitos de diferentes métodos de processamento sobre o tempo de cocção e nas características tecnológicas de arroz integral - Souza, Christian Rafael Câmara de (2019)
The objective of this study was to evaluate the effects of different processing methods on the cooking time and on the technological characteristics of brown rice. The methods studied were: I) hydration and drying (HD); II) hydration, freezing and drying and (HFD) and III) partial grain polishing (PGP). Being performed assessments of yield, degree of humidity, index of cracks (IC), colorimetric profile, acidity index and minimum cooking time (MCT). The results demonstrated that the HD method increased the IC that went from 2% in the standard sample to 97%, and decreased the MCT from 20 to 14 minutes, not influencing the moisture contents which remained around 10%, on yield of whole and broken grains which presented values around 97.70% and 2,50% respectively, and at the acid value which was around 0.55 mg KOH / g sample. Similarly, the HFD method increased the IC, decreased MCT from 20 to 16 minutes, reduced whole grains and increased broken grains. In the case of PGP, there was an increase in the IC and decreased of MCT, from 20 to 12 minutes in the polish of 10%, however considering keep a larger fraction of the bran, polishing with up to 2% reduced the MCT to 14.67 minutes, and reduced whole grains from 97% to 93%. It was concluded that the HD method was the most appropriate, because it reduced the MCT by 30%, not influencing the yield of whole grains, besides maintaining the technological characteristics of the grains.